Effect of inhalation of single dose of beclomethasone on airway epithelium - Uhlík, Jiří; Vajner, Luděk; Adášková, Jana; Konrádová, Václava (Ultrastructural pathology, 2007)
Inhaled corticosteroids are being recommended for the treatment of bronchial asthma for their anti-inflammatory properties and reduction of airway hyperreactivity. The first tissue coming to the contact with all inhaled substances is the airway epithelium. In this experiment, the immediate effect of a single MDI dose of beclomethasone on the ultrastructure of the tracheal and bronchiolar epithelium was studied. Due to the beclomethasone administration, the secretory elements were highly affected. The tracheal goblet cells were damaged, mucus release was significantly accelerated, and the mechanism of secretion was influenced. The bronchiolar Clara cells revealed signs of the pathological alteration. Their secretory granules were usually stored in the cytoplasm. Occasionally, degenerating Clara cells were found after the beclomethasone administration. The injury of ciliated cells in both locations was only mild and this fact was reflected in slight impairment of the tracheal ciliary border. As a morphological sign of impaired self-cleaning ability, inspissated secretion was discovered among cilia. According to this evaluation, the inhalation of the single dose of beclomethasone caused a moderate damage to the tracheal epithelium and a mild one to the epithelium of terminal bronchioles. The results draw attention to the adverse effects of otherwise therapeutically beneficial inhaled glucocorticosteroids.
Keywords: financování organizované; Animals; Anti-Asthmatic Agents; Microscopy, Electron, Transmission; Rabbits; respirační sliznice; Bronchi; beklomethason; pohárkové buňky; antiastmatika; bronchy; hlen; inhalační expozice; Financing, Organized; Mucus; Beclomethasone; Goblet Cells; Specific Pathogen-Free Organisms; králíci; Respiratory Mucosa; transmisní elektronová mikroskopie; zvířata; aplikace inhalační; Administration, Inhalation; Inhalation Exposure; organismy bez specifických patogenů